Contribution of mast cells to injury mechanisms in a mouse model of pediatric traumatic brain injury. Issue 12 (10th September 2016) - Moretti, Raffaella; Chhor, Vibol; Bettati, Donatella; Banino, Elena; De Lucia, Silvana; Le Charpentier, Tifenn; Lebon, Sophie; Schwendimann, Leslie; Pansiot, Julien; Rasika, Sowmyalakshmi; Degos, Vincent; Titomanlio, Luigi; et al.
Abstract : The cognitive and behavioral deficits caused by traumatic brain injury (TBI) to the immature brain are more severe and persistent than injuries to the adult brain. Understanding this developmental sensitivity is critical because children under 4 years of age of sustain TBI more frequently than any other age group. One of the first events after TBI is the infiltration and degranulation of mast cells (MCs) in the brain, releasing a range of immunomodulatory substances; inhibition of these cells is neuroprotective in other types of neonatal brain injury. This study investigates for the first time the role of MCs in mediating injury in a P7 mouse model of pediatric contusion‐induced TBI. We show that various neural cell types express histamine receptors and that histamine exacerbates excitotoxic cell death in primary cultured neurons. Cromoglycate, an inhibitor of MC degranulation, altered the inflammatory phenotype of microglia activated by TBI, reversing several changes but accentuating others, when administered before TBI. However, without regard to the time of cromoglycate administration, inhibiting MC degranulation did not affect cell loss, as evaluated by ventricular dilatation or cleaved caspase‐3 labeling, or the density of activated microglia, neurons, or myelin. In double‐heterozygous cKit mutant mice lacking MCs, this overall lack of effect was confirmed. These results suggest that the role of MCs in this model of pediatric TBI is restricted to subtle effects and that they are unlikely to be viable neurotherapeutic targets. © 2016 Wiley Periodicals, Inc. Abstract : Pediatric traumatic brain injury (TBI) causes significant permanent disability, and there are no specific therapies. Targeting mast cells with pharmacologic and genetic approaches, we found no effects on TBI severity, suggesting that mast cells are unlikely to play a significant role in pediatric TBI or to be viable targets for therapy.